Measurement Wavelength on Brass Plated Tire Steel Cord using Local Minima and Maxima - et. al, April Lia Hananto , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The method of measuring the diameter in the picture of the Brass Steel Tire Cord with Pixel Distance and Sliding Window, produces an average value of 0.241 obtained by measuring Pixel Distance, when using a sliding window, the average measurement result is 0.238, the accuracy of both methods of measuring the diameter of Cord Steel Tire Brass is considered quite good, the average results obtained from 29 Steel Tire Brass Cord data set samples (April Lia Hananto et al., 2020). The problem obtained in the conventional measurement phase of wavelengths on the Brass Cord Tire Cord is that the resulting accuracy still requires an observation process from an officer who is considered an expert, there is a possibility of error in his observation (Bouchet et al., 2003). In this study will change the measurement process using computer vision techniques using image processing (Tateno et al., 2020). The method used in the measurement of the wavelengths uses Local Minima and Maxima with approaches to the Wavelengths method. The results obtained by the average measurement can be recognized as its level of accuracy and close to the standard value of the measurement company.